Analisis Peran Employee Engagement dalam Meningkatkan Kinerja dan Komitmen Karyawan: Studi Kasus pada Apotek Bugel Godong Grobogan - Astuti, Dewi; Rahayu, Enik (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the role of employee engagement in enhancing employee performance and commitment at Bugel Godong Pharmacy, Grobogan. The research focuses on how the level of employee engagement influences performance and commitment, and how commitment functions as a bridge between the two. A qualitative approach was employed, using in-depth interviews, observations, and documentation to obtain comprehensive data. Data were analyzed interactively through reduction, presentation, and conclusion drawing stages. The results indicate that the level of employee engagement at Bugel Godong Pharmacy is relatively high (around 80%), particularly in work responsibility, teamwork, and managerial support. Strong engagement has been proven to increase productivity by 15–20% and reduce administrative errors by 15%. Affective commitment emerged as a key factor strengthening the link between engagement and performance, where employees who feel valued and supported demonstrate greater loyalty and motivation. This study concludes that organizational success at Bugel Godong Pharmacy depends not only on technical competence but also on the organization’s ability to create a supportive work environment that fosters emotional involvement, open communication, and harmonious relationships. These elements are essential in building commitment and improving employee performance sustainably.